Indonesian Banking Financial Performance on Profitability Using Panel Data Regression - Afriansyah, Riki; Pidaryani; Pratama, Muhammad Setya (Universitas Muhammadiyah Prof. DR HAMKA., 2024)
This study's goal is to determine if the return on assets (ROA) variable posted on the Indonesia Stock Exchange, together with the loan-to-deposit ratio (LDR), capital adequacy ratio (CAR), and non-performing loans (NPL), are correlated with profitability. The impact of return on assets (ROA) factors on the banking sector is investigated in this study. The research used a data sample of 245 from 49 financial institutions that have continuously fulfilled the necessary data requirements for a minimum of five years. Panel data, testing of panel data, testing of classical assumptions, and multiple regression analysis employing econometric views (E-views 12) are among the chosen analytical techniques. The ROA variable is unaffected by the LDR variable's t-test findings. In a similar vein, the ROA variable is unaffected by the t-test findings for the CAR variable. Moreover, the ROA variable is unaffected by the NPL variable's t-test findings. Nonetheless, the ROA variable is concurrently impacted by the LDR, CAR, and NPL factors.